REFLEKSI KONSONAN PROTOAUSTRONESIA MENJADI KONSONAN RANGKAP HOMORGAN BAHASA MADURA [Reflection Protoaustronesian to Consonant Cluster Homorgan in Madurese Language] - Dianita Indrawati (TOTOBUANG, 2016)
This paper discussdabout consonant reflection of Proto-Austronesian that became consonant cluster of homorgan Madurese language in comparative historical linguistic perspective. In the language of Madura, consonant cluster or clusters have homorgan and duplicate identical. It mean that, the double consonants are the same consonants. Consonant cluster was a reflection of a single consonant and consonant cluster Proto-Austronesian. Almost all consonants in the language of Madura was  consonant cluster identity. The Reflection consonant of Proto-Austronesian which became consonant cluster ofMadurese language can be seen through  analogy, assimilation, dissimilation, linear inheritance, and inheritance with the changes.Makalah ini membahas refleksi konsonan Proto-Austronesia menjadi konsonan rangkap homorgan bahasa Madura dalam perspektif linguistik historis komparatif.  Dalam bahasa Madura, konsonan rangkap atau gugus konsonan ada yang yang homorgan dan rangkap identik. Artinya, konsonan rangkap itu merupakan konsonan yang sama.  Konsonan rangkap tersebut merupakan refleksi dari konsonan tunggal dan konsonan rangkap Proto-Austronesia.  Hampir semua konsonan dalam bahasa Madura merupakan konsonan rangkap identik. Refleksi konsonan Proto-Austronesia menjadi konsonan rangkap bahasa Madura dapat melalui analogi, asimilasi, disimilasi, pewarisan linier, dan pewarisan dengan perubahan.